Legal Review of Embezzlement of Funds in Corporate Crimes - Sastradinata, Dhevi Nayasari; Nahdliyah, Hadziqotun; Sidiq, Kidung Alfiani (Jurnal Independent, 2024)
ABSTRACT One prevalent form of criminal offense within society is embezzlement, and this crime continues to occur across various sectors of society, spanning individuals from different socioeconomic backgrounds. This research aims to examine how embezzlement of funds is regulated within a corporation and to explore the accountability of embezzlers in corporate crimes. The study employs a juridical normative method, utilizing primary legal resources. The findings indicate that implementing direct criminal accountability on public corporations in the context of embezzlement unveils several relevant considerations. Placing public corporations as entities directly responsible for criminal acts sends a strong signal that any unlawful actions will not be tolerated, regardless of the perpetrators within the corporation. Involving senior officials or corporate leaders in criminal accountability encourages transparency and accountability within the corporate leadership structure, emphasizing the importance of integrity in decision-making processes. The restitution of rights for aggrieved victims emerges as a key aspect in addressing embezzlement crimes.